Phototriggered drug delivery using inorganic nanomaterials - Liu, Qian (Bioconjug Chem, 2016)
Light has many desirable properties as the stimulus for triggerable drug delivery systems. Inorganic nanomaterials are often key components in transducing light into drug delivery events. The nature of the light and the inorganic materials can affect the efficacy and safety of the drug delivery system.